Design and fabrication of concentrated solar thermal (CST) system for solar cooker application - Jolhi, Brahim (2010)
This report is about the design and fabrication of concentrated solar thermal system for solar cooker application. This project encourages the study of concentrated solar thermal system and also the solar cooker. Solar cooker is a device used for cooking application using the energy from the sun light. Concentrated solar thermal system help the solar cooker to gain a better heat concentration. Project is start with the study and research. From the information gathered from the literature study, four designs had been created. One of the designs is chosen using design screening process and modification is made. With the final design, fabrication is started. The process involves in fabrication are cutting, glass fibre works, arc welding and glass fibre’s moulding process. When the product is finished, it is tested to determine the temperature obtained and to prove that the product is working and success. Any further problem and recommendation regarding the product is discussed on the last chapter.